Patient Satisfaction With The One Day Cataract Surgery - Kola?ko, Štefanija; Hošnjak, Ana Marija; Juri?, Marina; Lueti?, Franka; Hodak, Jelena (Journal of Medical Biomedical and Applied Sciences, 2019)
PURPOSE: The aim was to determine the degree of patient satisfaction with the one day cataract surgery and detect critical points that could serve as a basis for the future improvements. METHODS: In this research, the occasional samples were the patients who came for grey cataract surgery, and passed through the outpatient clinic. The criteria for including patients in the research were that they came for cataract surgery and were admitted through outpatient clinic. None of the patients were excluded from the research and none of them were retrospectively included.The data in this study was collected by an anonymous questionnaire created for the needs of this research. The questionnaire was filled after the surgery procedure RESULTS: Statistical analysis of the obtained dana showed that the majority of patients, 130 (87.2%) of them, are satisfied with the cataract surgery, 12 (8.1%) are partially satisfied and the minimum number of patients, only two of them, are somewhat dissatisfied with the operation. There is no patient who is unhappy with the cataract surgery. CONCLUSIONS: Studies have shown that hospitalization is an especially traumatic and stressful experience, which is greatly reduces with the introduction of the daily hospital care.